Individual and community level determinants of iron intake among children 6-59 months old in Ethiopia: multilevel logistic regression analysis - Daniel Gashaneh Belay; Melaku Hunie Asratie; Anteneh Ayelign Kibret; Kegnie Shitu; Dawit Tefera Fentie; Yalelet Fentaw Shiferaw; Baye Tsegaye Amlak (BMC, 2022)
Abstract Background Iron deficiency is one of the most important factors of anemia which is caused by poor iron intake. In addition, children need more iron because of their rapid growth. On the other side, daily intake of iron is also recommended as a standard approach for the treatment and prevention of iron deficiency anemia. In Ethiopia, although more than half of children 6-59 months of age were affected by anemia, the magnitude and factors associated with iron intake among them are understudied. Therefore this study aimed to assess the magnitude and community and individual level determinants of iron intake among 6-59 months children in Ethiopia. Methods Demographic and Health Survey datasets (EDHS) were used for this study. The data were weighted using sampling weight to get valid statistical estimates. The total weighted samples of 9,218 children aged 6-59 months were included. A multilevel binary logistic regression model was fitted to identify factors associated with iron intake among 6-59 months of children in Ethiopia. In the final model adjusted odds ratio with a 95% confidence interval and p-value < 0.05 was taken to declare statistical significance. Results The magnitude of iron intake among children 6-59 months in Ethiopia was 9.24% (95% CI: 8.31%, 10.15%). Individual level variables such as having at least one antenatal care visit (ANC) [AOR = 1.27; 95%CI; 1.01, 1.61], having health institution delivery [AOR = 1.46; 95%CI;1.04, 2.04], age of children ≥ 24 months [AOR = 1.82; 95%CI; 1.29, 2.57], being female child [AOR = 0.81; 95%CI; 0.67, 0.99], being greater than three birth order [AOR = 0.73, 95%CI: 0.55, 0.98], whereas community level variables such as living in large central regions [AOR = 3.68; 95%CI; 1.47, 9.21], and living in community with high women education [AOR = 1.96; 95%CI; 1.28, 2.98] have an association with iron supplements among children 6-59 months years old in Ethiopia. Conclusion and recommendations The magnitude of iron intake among children 6-59 months old in Ethiopia is relatively low. Individual level factors such as; ANC visit, institution delivery, age of children, sex of the child, and birth order as well as; community level variables such as regions, and community women's education have a significant association with iron intake among children 6-59 months in Ethiopia. Prior attention should be given for under two years old children, children greater than three birth orders, and children living in small peripheral regions. Moreover, policymakers and other stakeholders had better plan and implement programs that empower women, enhance ANC visits, and health institution delivery to have a sustainable increment in iron intake for children in Ethiopia.